Pseudo-relaxor behavior in 0.35La2O3–0.65Nb2O5 glass prepared by aerodynamic levitation method. (June 2016) - Zhang, Zhanpei; Li, Haibo; Wang, Chunchang; Li, Jianqiang; Ma, Xiaoguang
Graphical abstract: Highlights: The glass was prepared by aerodynamic levitation method. A temperature and frequency-independent dielectric constant ( ε r ≈ 40 ) under 473 K A relaxor-like behavior was observed above 200 °C. The low-temperature relaxation is a conduction relaxation. The other one is a Maxwell-Wagner relaxation associated with phase boundary. Abstract: 0.35La2 O3  − 0.65Nb2 O5 glasses were prepared by aerodynamic levitation method. The dielectric properties of the sample were investigated as a function of temperature (30 − 700 °C) in the frequency range from 100 Hz to 1 MHz. The glasses show a temperature and frequency-independent dielectric constant of ∼40 below 200 °C. A relaxor-like behavior was observed above 200 °C, which was found to be composed of two relaxations with the activation energy of 1.32 eV and 1.3 eV for the low- and high-temperature relaxations, respectively. Impedance analysis reveals that the low-temperature relaxation is a conduction relaxation associated with hopping motion of oxygen ions and the high-temperature one is a Maxwell-Wagner relaxation associated with phase boundary. The relaxor-like behavior is attributed to the combining effect of both relaxations.